1996
DOI: 10.1007/bf00183121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on urethral function

Abstract: Urethral pressure profiles (in vivo), opening pressures, and flow rates at opening pressure (in vitro) were determined for female, male, pregnant, ovariectomized (OVX), OVX and then estrogen-treated, and OVX and then progesterone-treated rabbits. Using the isolated whole-urethra preparation, we determined the opening pressures and flow rates as well as the effects of 250 microM phenylephrine, 250 microM bethanechol, and 120 mM KCl on the urethral opening pressure and flow rate. The results demonstrated that (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…17 Our pharmacological studies confirm previous observations that UP is under the influence of smooth as well as striated muscles. 14,18,19 To our knowledge the novel aspect of our study is that not 1 but 2 skeletal muscle components, ie the RHB and PRM, contribute to urethral pressure. PRM contraction increases pressure in all 3 orifices, ie urethra, vagina and anal canal.…”
Section: Discussionmentioning
confidence: 98%
“…17 Our pharmacological studies confirm previous observations that UP is under the influence of smooth as well as striated muscles. 14,18,19 To our knowledge the novel aspect of our study is that not 1 but 2 skeletal muscle components, ie the RHB and PRM, contribute to urethral pressure. PRM contraction increases pressure in all 3 orifices, ie urethra, vagina and anal canal.…”
Section: Discussionmentioning
confidence: 98%
“…Another study showed that urinary incontinence symptoms of stress and urgent urine worsened when menopausal women with menopause were given both estrogen and P4 . Habib et al . reported that P4 was not shown to have an effect on urethral pressure in a study of female ovariectomy rabbits after administering P4.…”
Section: Discussionmentioning
confidence: 99%